Broadband Resonant Elements for 5G Reflectarray Antenna Design - M. Hashim Dahri; M. R. Kamarudin; M. H. Jamaluddin; M. Inam; R. Selvaraju (Universitas Ahmad Dahlan, 2017)
The performance investigation of two novel resonant elements is presented in this work for 5G reflectarray antenna design. Two dual resonance elements with wide reflection phase range have been developed from a square patch element by a novel corner bending tactic. The reflection loss and reflection phase range performance of the proposed elements have been compared with conventional square patch element at 26 GHz. The results have shown a reflection phase swing of 629° and 632° for Bent Width and Bent Length elements respectively. The broadband features of proposed elements can radically improve the bandwidth performance of a reflectarray antenna.